On wavelet type Bernstein operators - Karsli, H. (Carpathian Mathematical Publications, 2023)
This paper deals with construction and studying wavelet type Bernstein operators by using the compactly supported Daubechies wavelets of the given function f. The basis used in this construction is the wavelet expansion of the function f instead of its rational sampling values f( kn). After that, we investigate some properties of these operators in some function spaces.